Impact of Socio-economic Class on Colorectal Cancer Patient Outcomes in Kuala Lumpur and Kuching, Malaysia - Kong, Chee Kwan; Roslani, April Camilla; Law, Chee Wei; Law, Diana Suk Chin; Arumugam, Kulenthran (Asian Pacific Organization for Cancer Prevention, 2010)
Objective: Research over the past several decades has indicated that low socioeconomic class has a direct effect on health outcomes. In Malaysia, class distribution may differ with the region. The objective of this study was to compare the presentation and survival of colorectal cancer patients in two dissimilar cities, Kuala Lumpur and Kuching, Sarawak.